Better cardiac care: health professional's perspectives of the barriers and enablers of health communication and education with patients of Aboriginal and Torres Strait Islander descent - Jordan Stanford; Karen Charlton; Anne-Therese McMahon; Scott Winch (BMC, 2019)
Abstract Background A body of knowledge continues to grow regarding Aboriginal perspectives on current challenges and barriers to health literacy and access to health services. However, less is known from the perspectives of health professionals who work in cardiac care. Given their role in delivering patient education, health practitioners could provide useful insights into potential solutions to improve patient-practitioner communication. The primary aim was to explore perspectives of health professionals who work in coronary care units regarding the enablers, barriers and potential solutions for patient-practitioner communication with patients of Aboriginal and Torres Strait Islanders descent. The secondary aim was to evaluate the acceptability and value of two videos developed with key stakeholders to provide culturally appropriate education. Methods Participants were recruited from two major regional hospitals. In-depth, semi-structured interviews were conducted with 17 health professionals (11 Nurses, five Cardiologists and one Aboriginal Health Worker). Interviews were recorded, de-identified and transcribed verbatim. Transcripts were analysed using constant comparison, interpreted through inductive thematic analysis and final themes were agreed through consensus with secondary researcher. Results Health professionals acknowledged that existing barriers resulted from organisational structures entrenched in the healthcare system, impacted on the practitioners' ability to provide culturally appropriate, patient-centred care. Lack of time, availability of culturally appropriate resources and the disconnection between Western medical and Aboriginal views of health were the most common challenges reported. The two videos evaluated as part of this study were found to be a useful addition to practice. Strengths in the videos design were the use of Aboriginal and Torres Strait Islander actors and positive messaging to convey health related topics. Further improvements included additional information related to common tests and procedures to allow for realistic expectations of patient care. Conclusion Re-modelling of organisational structures is required in order to promote a more culturally-friendly and welcoming environment to encourage Aboriginal and Torres Strait Islanders to engage with mainstream cardiac care services. The videos that were developed using principles that are sensitive to Aboriginal health views, may offer an additional way in which to overcome existing barriers to effective patient-practitioner communication with Aboriginal and Torres Strait Islanders.